(untitled) (Actualité en allergologie et en immunologie au Canada, 2024)
Many oral abstracts, posters and case reports were presented at The European Academy of Allergy and Clinical Immunology (EAACI) Annual Meeting which was held in June 2024 in Valencia, Spain. We have selected the following 13 articles due to their relevance to Canadian allergy and immunology clinical practice and research.